A new species of pouched octopus, Cistopus Gray, 1849 (Cephalopoda: Octopodidae) from the southwest coast of India - Sreeja, Vijayamma; Norman, Mark D.; Kumar, Appukuttannair Biju (Zootaxa, 2015)
Octopuses of the genus Cistopus Gray, 1849 are commercially valuable catches in the cephalopod fisheries of India. The primary and unique diagnostic character of this genus is the possession of eight small mucous pouches embedded in the oral faces of the webs between the bases of each arm. Historically only a single species of Cistopus, C. indicus, had been reported from Indian waters. In reviewing the octopod fauna off the Kerala coast, we have detected three species of Cistopus, of which one is described here as a new species. Cistopus platinoidus sp. nov. is distinct from Cistopus species described to date (C. indicus, C. taiwanicus and C. chinensis) on the basis of sucker counts, the number and position of enlarged suckers in males, and presence/absence of a calamus. Our studies of catch composition of Kerala octopod fisheries indicate a higher diversity of target species than previously suspected, including a number of undescribed species. Taxonomic resolution and collation of biological and distributional data are required for effective monitoring and management of these valuable fisheries.